Effects of ivermectin on cytokine and immunoglobulin levels in sheep - Canbar, Rahmi; Dik, Irmak; Uslu, Muhittin; Ider, Merve; Arslan, Mustafa-Sedat; Yazar, Enver (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Ivermectin may affect the levels of cytokines and immunoglobulins in sheep, considering that avermectins have an effect on the immune system. Objective: To determine whether ivermectin has an effect on cytokines and immunoglobulins in sheep. Methods: After administration of ivermectin to 10 healthy sheep, sheep-specific interferon-α, tumor necrosis factor-α, interleukin-2, interleukin-6, interleukin-10, immunoglobulin G, immunoglobulin M, and immunoglobulin E levels were measured with an ELISA reader. Results: Significant (p<0.05) fluctuations were detected in interleukin-2 and interleukin-10 levels. Transient increases (p<0.05) were measured in tumor necrosis factor-α and immunoglobulin E levels (p<0.05). Conclusion: Ivermectin may affect immune system parameters in healthy sheep; however, the effects of ivermectin administration on infected sheep should be investigated.